The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.22409/1984-0292/2022/v34/28423
|View full text |Cite
|
Sign up to set email alerts
|

Mães de bebês em UTIN: rede de apoio e estratégias de enfrentamento

Abstract: A Unidade de Terapia Intensiva Neonatal (UTIN), embora seja um ambiente de cuidados especiais para garantir a sobrevivência de recém-nascidos, tende a suscitar, nas mães e familiares, percepções e sentimentos ambíguos sobre os eventos relacionados a internação e, ainda, alterar a saúde emocional dos envolvidos. O presente estudo teve como objetivo verificar a associação entre apoio social, estratégias de enfrentamento e tempo de internação, de mães de bebês em UTIN. Os dados foram obtidos de uma amostra de 50 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
0
0
3

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 12 publications
0
0
0
3
Order By: Relevance
“…Contrasting the results, a study carried out in Turkey with 906 postpartum women showed that fear of COVID-19 was associated with socioeconomic variables such as high level of education, high income and paid activity (35) . However, in this same study, it was found that women undergoing cesarean section reported high fear of COVID-19, indicating that hospital admission and interventions can influence and increase the feeling of fear (36) , similarly to the result that pointed to the association between high fear and NB admission.…”
Section: Discussionsupporting
confidence: 53%
“…Contrasting the results, a study carried out in Turkey with 906 postpartum women showed that fear of COVID-19 was associated with socioeconomic variables such as high level of education, high income and paid activity (35) . However, in this same study, it was found that women undergoing cesarean section reported high fear of COVID-19, indicating that hospital admission and interventions can influence and increase the feeling of fear (36) , similarly to the result that pointed to the association between high fear and NB admission.…”
Section: Discussionsupporting
confidence: 53%
“…Contrapondo os resultados, um estudo realizado na Turquia com 906 puérperas evidenciou que o medo da COVID-19 esteve associado a variáveis socioeconômicas como alto nível de escolaridade, alta renda e exercício de atividade remunerada (35) . No entanto, neste mesmo estudo, constatou-se que mulheres submetidas à cesárea relataram alto medo da COVID-19, indicando que a hospitalização e as intervenções podem influenciar e aumentar a sensação de medo (36) , semelhantemente ao resultado que apontou a associação entre o alto medo e a hospitalização do RN.…”
Section: Discussionunclassified
“…El período neonatal que comprende los primeros 28 días de vida es considerado una fase de gran fragilidad, ya que se relaciona con la fase correspondiente a la adaptación extrauterina (1) . Se evidencia como la más vulnerable para la supervivencia del recién nacido (RN) (2) , así, la asistencia de calidad que parte del prenatal, como los servicios ofrecidos desde el nacimiento hasta el alta hospitalaria, posibilitan la reducción de lesiones y una mejor calidad de vida para los recién nacidos (3) . Dentro de este período, pueden ocurrir cambios influenciados por riesgos ambientales, biológicos, socioeconómicos, culturales, así como condiciones maternas (4) .…”
Section: Introductionunclassified
“…Dentro de este período, pueden ocurrir cambios influenciados por riesgos ambientales, biológicos, socioeconómicos, culturales, así como condiciones maternas (4) . Las muertes neonatales alcanzan aproximadamente 3 millones en el mundo, siendo la prematuridad la principal causa, donde el 46% de las muertes de niños menores de cinco años ocurren en sus primeros días de vida (1)(2)(3)(4) .…”
Section: Introductionunclassified
See 1 more Smart Citation